Synthesis of (+/-)-thia-calanolide A, its resolution and in vitro biological evaluation - Chopade, Anil U.; Chopade, Manojkumar U.; Chanda, Bhanu M.; Sawaikar, Dilip D.; Sonawane, Kiran B.; Gurjar, Mukund K. (Arabian Journal of Chemistry, 2016)
A synthesis of (+/-)-thia-calanolide A 3 has been successfully accomplished starting from 3,5-dimethoxythiophenol 4, in six steps in an overall yield of 4.5%. The key reaction involved Friedel-Crafts tigloylation of 5,7-dihydroxy-4-n-propyl thiocoumarin 6 employing an appropriate solvent of CS2-PhNO2 in a ratio of 7:3. In its biological evaluation for anti-HIV activity, (+/-)-thia-calanolide A 3 demonstrated comparatively less activity with calanolide A and its synthetic analogue aza-calanolide. Further, (+/-)-3 has been resolved by chiral HPLC to (+) and (-)-3. (C) 2012 Production and hosting by Elsevier B.V. on behalf of King Saud University.